2016
DOI: 10.1007/s00264-016-3123-5
|View full text |Cite
|
Sign up to set email alerts
|

Individualised distal femoral cut improves femoral component placement and limb alignment during total knee replacement in knees with moderate and severe varus deformity

Abstract: Level 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Our results showing variation in VCA between the varus and valgus knee in windswept knees undergoing TKA is validated by similar studies done by other investigators in arthritic knees undergoing TKA. Mullaji et al, 4 in an analysis of 503 knees undergoing TKA reported that 56% of knees had VCA outside the usual range of 5-78 whereas Palanisami et al, 5 in an analysis of 227 knees reported that 31% of knees had VCA outside the usual range of 5-78. This is similar to our study where 38% of knees had VCA outside the usual range of 5-78.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showing variation in VCA between the varus and valgus knee in windswept knees undergoing TKA is validated by similar studies done by other investigators in arthritic knees undergoing TKA. Mullaji et al, 4 in an analysis of 503 knees undergoing TKA reported that 56% of knees had VCA outside the usual range of 5-78 whereas Palanisami et al, 5 in an analysis of 227 knees reported that 31% of knees had VCA outside the usual range of 5-78. This is similar to our study where 38% of knees had VCA outside the usual range of 5-78.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Individualising the VCA is crucial during TKA in order to achieve accurate limb and femoral component alignment and minimising errors especially in the presence of severe deformity or excessive femoral bowing of the femoral shaft. 5,7 Hence, in view of the significant difference in mean VCA between the varus and the valgus knee, windswept deformities undergoing TKA is an indication for the surgeon to preoperatively measure femoral VCA on full-length hip-to-ankle radiographs in order to minimise error. Limitations of this study include the retrospective nature of the study with its inherent drawbacks and biases and a relatively small number of study subjects considering the inherent rarity of windswept deformity in arthritic knees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Mullaji et al reported that 56% of 503 knees undergoing TKA had VCA outside the normal range of 5°-7° [ 14]. Shetty et al reported that 38% of 100 knees undergoing TKA had VCA outside the range of 5°-7° [15]; Palanisami et al reported 31% of 227 knees undergoing TKA had VCA outside 5°-7° [16]. The results of our research measured by 3D indicated that 18% of 112 knees of normal volunteers had VCA outside 5°-7°; 56% of 100 knees of DDH patients had VCA outside 5°-7°.…”
Section: Discussionmentioning
confidence: 99%
“…However, the femora of some DDH patients are usually abnormal in femoral bowing. In such cases, the intramedullary rod implanted into a distal femur along with the femoral anatomical axis can cause stress concentration and fracture [16]. The lower VCA is more in line with the operation in these cases compared to the upper VCA.…”
Section: Discussionmentioning
confidence: 99%